Seasonal and inter-annual variability of chemotaxonomic marker pigments in the north-eastern Arabian Sea. (January 2022) - Chndrasekhararao, A.V.; Kurian, Siby; Vidya, P.J.; Gauns, Mangesh
Abstract: Using in situ data, the present study explored the seasonal and inter-annual variations of phytoplankton characteristics in the north-eastern Arabian Sea (NEAS). Phytoplankton pigment assessment was carried out at the Arabian Sea Time Series (ASTS) site in the NEAS (17°N 68°E) over 2011–2017 during the late south-west monsoon (SWM) and north-east monsoon (NEM). The site is largely influenced by open ocean upwelling during the SWM and winter convective mixing during the NEM, enhancing the productivity of the region. Winter convective mixing led to high biomass in the euphotic zone during the NEM, while late SWM showed oligotrophic conditions with subsurface chlorophyll maxima (Chlmax ). Our measurements showed that the NEM supports larger phytoplankton, whereas the late SWM supports smaller groups, highlighting the crucial role of picoplankton in the productivity of the NEAS. Microscopic observation (cells >10 μm in size) also supported the presence of a higher number of diatoms and dinoflagellates during the NEM as compared to those during the late SWM. Among the picoplankton, Prochlorococcus counts were high during the late SWM than the NEM, which is also reflected in marker pigments. Apart from the seasonal variability, the region also showed large inter-annual variability which was checked with reference to the climate modes such as El-Niña Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). Though IOD influence was not distinct on phytoplankton composition in the NEAS during the late SWM, the upper ocean variability during the ENSO resulted in a large contribution of picoplankton in the following NEM. We also compared the pigment data at ASTS with station N9 of US- Joint Global Ocean Flux Study (JGOFS) collected during 1995, as these stations are very close to each other. Though the marker pigments during the recent years were comparable to those of US-JGOFS, large inter-annual variability makes it difficult to interpret long-term changes in the phytoplankton composition. The present study recommends the need for sustained long-term time-series observations in the Arabian Sea to understand the changes in phytoplankton composition under the climate change scenario. Highlights: Phytoplankton pigment assessment at the ASTS site in the NEAS over 2011 - 2017 showed seasonal variability. NEM supports larger phytoplankton, whereas late SWM supports smaller groups, however with large inter-annual variability. Microscopic observation also supported higher number of diatoms and dinoflagellates during the NEM as compared to late SWM. The upper ocean variability during the ENSO resulted in a large contribution of picoplankton in the following NEM. Recommends the need for sustained long-term time-series observations in the AS to understand the shift in phytoplankton.